Impact of ferromagnetic nanoparticles on magnetized Eyring–Powell nanofluid flow subject to magnetic dipole - Tabrez, M.; Khan, W. A.; Hussain, I.; Zubair, M. (International journal of modern physics. B, Condensed matter physics, statistical physics, applied physics, 2024)
Due to recent advancements in technologies and nanoscience, research focused on nanofluid because of its extensive use in many industrial as well as manufacturing processes. Nanotechnology is widely utilized in many photovoltaic devices, mini-computers, bio-medical apparatus, electronic instruments, cooling and heating of metallic plates, etc. In view of numerous applications, the basic aim of this work is to explore the impact of ferromagnetic nanomaterial on 2-D Eyring–Powell fluid flow. Characteristics of viscous dissipation and Brownian movement are under consideration. Some suitable similarity transformations are exploited to achieve the nonlinear ODEs from PDEs. Bvp4c scheme is implemented to solve the resultant system of equation. Impacts of ferromagnetic interaction parameter, thermophoresis parameter, viscous dissipation, Curie temperature and Eckert number are perceived for velocity, temperature as well as concentration fields. Moreover, velocity, thermal and mass transfer gradients are deliberated and scrutinized graphically. It is found that upsurge in the value of magnetic parameter reduces the velocity profile while it deteriorates against Eyring–Powell fluid parameter. Additionally, greater thermophoresis parameter has augmented the temperature profile while it shows opposite behavior for concentration.